Comparison of uniportal video-assisted thoracoscopic versus thoracotomy bronchial sleeve lobectomy with pulmonary arterioplasty for centrally located non-small-cell lung cancer. (17th November 2020) - Xie, Dong; Zhong, Yifan; Deng, Jiajun; She, Yunlang; Zhang, Lei; Fan, Jiang; Jiang, Gening; Zhu, Yuming; Jiang, Lei; Chen, Chang
Abstract:  : OBJECTIVES: This study aimed to investigate the efficacy of bronchial sleeve lobectomy with pulmonary arterioplasty by uniportal video-assisted thoracoscopic surgery (UniVATS) in centrally located non-small-cell lung cancer. METHODS: One hundred and two thoracotomy and 31 UniVATS cases were included in this retrospective, single-centre study. Baseline characteristics, perioperative performance and survival outcomes were compared between the 2 groups. RESULTS: Compared with the thoracotomy group, the UniVATS group was associated with lower postoperative blood transfusion rate ( P  =   0.043), decreased postoperative hospital stays ( P  =   0.008), shorter drainage duration ( P  =   0.003) and less drainage volume during the first postoperative 24 h ( P  =   0.005). Besides, the 3-year overall survival and recurrence-free survival were comparable between the 2 groups (log-rank, P  =   0.81 and P  =   0.78, respectively). In addition, squamous cell carcinoma was proved to be the independent favourable predictor for overall survival [hazard ratio (HR) 0.44, 95% confidence interval (CI) 0.24–0.80; P  =   0.008], and advanced pathological stage was found to be independently associated with worse overall survival (IIIB stage: HR 3.21, 95% CI 1.13–9.12; P  =   0.028) and recurrence-free survival (IIIB stage: HR 3.54, 95% CI 1.32–9.51; P  =   0.012). CONCLUSIONS: With appropriate patient selection, UniVATS sleeve lobectomy with pulmonary arterioplasty is feasible and safe for centrally located lung cancer in the hands of thoracic surgeons with extensive thoracoscopy experience.